Ames mutagenicity, structural alerts of carcinogenicity, Hansch QSAR parameters (ClogP, CMR, MgVol), tumor site concordance/multiplicity, and tumorigenicity rank in NTP 2-year rodent studies. (22nd February 2018) - Smith, Carr J; Perfetti, Thomas A; Ko, Gene M; Garg, Rajni
Since its inception in 1976, the National Toxicology Program (NTP) has conducted 594 2-year studies on rats and mice by a number of routes of administration including inhalation, feed, drinking water, dermal, and intraperitoneal injection. Of these studies, the results on 470 chemicals were of adequate technical quality to be incorporated into final technical reports. In this study, the 470 chemicals were categorized from 1 to 48 by the level of "clear" neoplastic evidence in male and female rats, and in male and female mice, and given an ordinal rank from 1 to 135 following additional considerations regarding tumor site concordance and tumor multiplicity. The resultant tumorigenicity category score and ordinal rank score were examined for associations with results in the Ames Salmonella mutagenicity assay; presence or absence of structural alerts of carcinogenicity; and three Hansch Quantitative Structure-Activity Relationship (QSAR) parameters, namely, calculated base 10 logarithm of the octanol–water partition coefficient (ClogP), calculated molar refractivity (CMR), and McGowan molecular volume (MgVol). Smaller molecular volumes were found to be associated with higher levels of tumorigenicity. Whereas lower rather than higher levels of lipophilicity were found to be associated with higher levels of tumorigenicity. Positive Ames test results were positively correlated with overall tumorigenicity and with possession of structural alerts. Since larger organic molecules have more chemical reaction centers, it was not surprising that higher ClogP values were positively correlated with the number of structural alerts. The results from this study demonstrate the ability to devise rational rules for relative tumorigenicity that correlate, in biologically plausible ways, with known parameters of toxicity.